Economic and ecological efficiency of adaptive system for fertilising spring barley - I. I. Gureev; A. V. Gostev; L. B. Nitchenko (Юг России: экология, развитие)
Aim. To determine the economic and environmental efficiency of a spring barley fertilizer system by adaptively eliminating nutritional deficiencies according to the functional diagnostics of plant leaves.Materials and Methods. Three‐year tests were conducted in a field experiment on spring barley. An adaptive innovative version of the experiment was oriented toward eliminating the deficit in plant nutrition by foliar fertilizing with complex fertilizers according to leaf functional diagnostics, which took into account the synergy of interaction between the applied elements. It was compared in terms of economic and environmental indicators with the option where top dressing on the leaves was carried out without taking into account the interaction between nutrients (additional control), as well as with the option without fertilizers (absolute control). The fertilizer requirement of the crop was determined using an Aquadonis portable laboratory. The synergy of interaction between the nutrients was assessed by diagnosing the need for each of them using a specially selected nutrient mixture, which allows us to formalise a model of interconnected factor space.Results. The high efficiency of using complex fertilizers in the cultivation of spring barley has been established. It is shown that the economical use of fertilizers is achieved by the adaptive elimination of their deficit according to foliar functional diagnostics, taking into account the synergy of interaction between the applied elements.Conclusion. The application of innovation with the equal quality of barley grain increased the annual saving of total costs from 1830 to 2571 roubles/ha, mainly due to the reduction of fertilizer costs. The innovation allowed a significant reduction in the amount of fertilizers used, which, together with the economic effect, also led to an environmental effect, i.e. environmental pollution by mineral fertilizers was decreased.